Understanding struvite crystallisation and recovery - Le Corre, Kristell S. (Cranfield University, 2006)
Struvite crystallisation from wastewater effluents is seen as an alternative to traditional biological and chemical phosphorus removal processes used widely in the wastewater treatment industry. It presents the advantage of not only removing phosphorus but also generating a compound that could be reused as a fertiliser. However the application of struvite crystallisation processes at full scale is not widespread due to the unknown economical value of the process and the product, the need of pH control, the necessity of long operational times to ensure quality of the product and the formation of crystal fines. Preliminary crystallisation experiments were carried out at laboratory scale to provide a better understanding of nucleation and growth processes, and identify how basic parameters such as pH, mixing energy, water chemistry or presence of foreign ions affected struvite crystallisation. Particular attention was paid to the quality (i.e. size, shape and purity) of the crystal formed. The results revealed that the presence of calcium ions in solution could alter struvite purity and even inhibit its formation. pH was also identified as a parameter of major impact on struvite crystal quality. Indeed, pH could either influence struvite purity or affect size of crystals formed. Further investigations in a purposely built reactor also revealed that if struvite crystallisation is relatively simple to achieve, the control of struvite quality and more particularly crystal size is complex. Results at pilot scale showed that reactor operation and struvite surface charge could be a limitation to its agglomerative properties, hence to the formation of larger crystals. To optimise struvite crystallisation and limit the problem of fines formation the present study has investigated two possible solutions: struvite fines recovery by coagulation or struvite crystallisation on seed materials. Struvite coagulation proved to be an efficient solution to remove and recover struvite fines rapidly through floc formation. Of the coagulant tested, polyDADMAC was the most effective resulting in the formation of flocs 10 times bigger than the initial size of crystals. With regards to crystallisation on seed materials, the results revealed that success of struvite attachment onto seeds in short contact times was only efficient when mixing energy in the reactor was limited. In that sense, the submersion of a metallic system in the reactor allowed excellent phosphorus removal and rapid struvite recovery in only 2 hours of operation.